Microfluidic formation of highly monodispersed multiple cored droplets using needle‐based system in parallel mode. Issue 10 (13th February 2020) - Lian, Zheng; Chan, Yue; Luo, Yang; Yang, Xiaogang; Koh, Kai Seng; Wang, Jing; Chen, George Zheng; Ren, Yong; He, Jun
Abstract: Scale‐up in droplet microfluidics achieved by increasing the number of devices running in parallel or increasing the droplet makers in the same device can compromise the narrow droplet‐size distribution, or requires high fabrication cost, when glass‐ or polymer‐based microdevices are used. This paper reports a novel way using parallelization of needle‐based microfluidic systems to form highly monodispersed droplets with enhanced production rates yet in cost‐effective way, even when forming higher order emulsions with complex inner structure. Parallelization of multiple needle‐based devices could be realized by applying commercially available two‐way connecters and 3D‐printed four‐way connectors. The production rates of droplets could be enhanced around fourfold (over 660 droplets/min) to eightfold (over 1300 droplets/min) by two‐way connecters and four‐way connectors, respectively, for the production of the same kind of droplets than a single droplet maker (160 droplets/min). Additionally, parallelization of four‐needle sets with each needle specification ranging from 34G to 20G allows for simultaneous generation of four groups of PDMS microdroplets with each group having distinct size yet high monodispersity (CV < 3%). Up to six cores can be encapsulated in double emulsion using two parallelly connected devices via tuning the capillary number of middle phase in a range of 1.31 × 10 −4 to 4.64 × 10 −4 . This study leads to enhanced production yields of droplets and enables the formation of groups of droplets simultaneously to meet extensive needs of biomedical and environmental applications, such as microcapsules with variable dosages for drug delivery or drug screening, or microcapsules with wide range of absorbent loadings for water treatment.